DNA microarray analysis of pancreatic malignancies - Brandt, Regine; Grützmann, Robert; Bauer, Andrea; Jesenofsky, Ralf; Ringel, Jörg; Löhr, J.-Matthias; Pilarsky, Christian; Hoheisel, Jörg D. (Pancreatology, 2004)
Pancreatic ductal adenocarcinoma (PDAC) has an extremely poor prognosis. To improve the prognosis, novel molecular markers and targets for earlier diagnosis and adjuvant and/or neoadjuvant treatment are needed. Recent advances in human genome research and high-throughput molecular technologies make it possible to cope with the molecular complexity of malignant tumors. With DNA array technology, mRNA expression levels of thousand of genes can be measured simultaneously in a single assay. As several studies using microarrays in PDAC have already been published, this review attempts to compare the published data and therefore to validate the results. In addition, the applied techniques are discussed in the context of pancreatic malignancies.
Elektronische Reproduktion der Druckausgabe
Gesehen am 24.05.2022